Komunikasi Interpersonal Orang Tua Dengan Remaja Dalam Mengatasi Kecanduan Game Online Di MTS Nurul Ihsan Peninjauan - Saean Hufron; M Arju Ghupran (Communication Studies Program Faculty of Social and Political Sciences Universitas Nurdin Hamzah Jambi, Indonesia, 2025)
The research aims to analyze how intrapersonal communication between parents and adolescents of MTS Nurul Ihsan who are addicted to online games. The Relational Dialectics theory from Leslie Baxter and Barbara Montgomery by paying attention to four aspects, namely, totality, contradiction, movement, and praxis. The results of the study are (totality) parents of adolescents addicted to online games are worried about the bad effects that occur to their children when excessive playing online games. Totality is the occurrence of one member in a relationship so that other members will be affected. The conflict between parents and teenagers addicted to online games is a difference of opinion or desire then this problem causes conflict (contradiction). The changes that occur are natural and must occur over time (movement). (praxis) teenagers decide to choose to reduce their time playing online games according to the rules made by their parents even though teenagers are personally reluctant to make these decisions because humans are decision makers even though they do not have full decision in free choice.